Hubungan Transformational Leadership terhadap Safety Culture pada Institusi Kesehatan: Sebuah Studi Telaah Literatur - Muhammad Dandy Fachrindra; Nuri Herachwati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study examines the relationship between Transformational Leadership and Safety Culture in healthcare institutions through a systematic literature review. Transformational leadership plays an important role in influencing the culture of their organizations and improving patient safety in healthcare. This study found that transformational leadership directly and indirectly positively impacts safety culture and patient safety outcomes, such as decreased adverse events and increased nurse job satisfaction. Several dimensions of transformational leadership, such as inspiration and intellectual stimulation, contribute to improved working conditions and safety culture in hospitals. This review highlights the need for further research, especially in a more diverse context, to strengthen understanding of the role of transformational leadership in strengthening safety culture in the health sector.